Intrahepatic subcapsular hematoma complicating laparoscopic cholecystectomy - Law, Chee Wei; Ng, Colin Leong Liong (Faculty of Medicine, University of Malaya, 2008)
A 65-year-old lady with cholelithiasis underwent an elective laparoscopic cholecystectomy (LC) and was discharged on post-operative day 2. She was re-admitted after five days with right hypochondriac pain and fever. Investigations revealed a drop in hemoglobin. Computed tomography showed a large intrahepatic subcapsular collection without intra-abdominal collection. She was treated with intravenous antibiotics. Percutaneous aspiration of intrahepatic subcapsular collection under ultrasound guidance revealed old blood. Hence diagnosis of intrahepatic subcapsular hematoma (ISH) was made. She improved and was discharged after a two weeks' hospital stay. Follow-up ultrasonography examination two months later revealed complete resolution of the hematoma. We report this case due to its rarity and review the previously documented cases of this complication.